Quantitative and qualitative instruments for knowledge management readiness assessment in universities - Agarwal, Naresh Kumar; Marouf, Laila (Qualitative and Quantitative Methods in Libraries, 2017)
Knowledge Management (KM) is the process of capturing, creating, disseminating and applying all forms of knowledge within an organization in order to fulfil one or more organizational objectives. However, universities have been slow to adopt Knowledge Management. Agarwal & Marouf (2014) came up with a 10-step process and a framework for initiating KM in universities. The steps were organized within 4 phases of plan, design, implement and scale-up. After getting top management support, forming a KM team, and identifying KM goals and priorities, the third step of their process (within the design phase) was determining the extent to which the university is ready for KM i.e. an assessment of its current state of readiness. Agarwal & Marouf propose that readiness assessment can be achieved through a survey, interview or focus groups to determine the KM capabilities relating to people, culture, processes and technology within the university. While there are a number of readiness assessment instruments, it is not clear how such instruments would look like in the context of universities and when surveying faculty members. What would be the quantitative and qualitative way of gathering KM readiness data in universities? In this study, we will design and propose a research model, a survey instrument, and an interview protocol for KM readiness assessment in universities. Readiness assessment could mean individual faculty readiness as well as organizational readiness. While the survey instrument will focus on individual faculty readiness, the interview protocol will focus on organizational factors. Where possible, survey items will be adapted from previous studies, and new ones developed where needed. The survey instrument and interview protocol could be used by other researchers to carry out mixed-method studies to assess individual KM readiness in universities. Future work will involve coming up with a survey instrument for organizational factors, and an interview protocol for individual factors, and then combining the instruments for both sets of factors.